Karakterisasi Zat Warna Tomat (Solanum lycopersicum) FRAKSI Metanol:N-Heksan Sebagai Photosensitizer Pada Dye Sensitized Solar Cell (DSSC) - Nur Hasbi Wahab; Aisyah Aisyah Aisyah; Suriani Suriani (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2016)
One of the potential alternative energy to be developed to overcome energy crisis in the world is an DSSC. This research aimed to make a series of Dye Sensitized Solar Cell (DSSC) using an organic dye from crude extract of tomato as a photosensitizer. The dye obtained from the maceration by of ultrasonic waves using methanol. Separation was done by KKCV using eluent of methanol: n-hexane (3: 7, 1: 1, 7: 3). The best efficiency value (Ƞ) in the series of DSSC that results from the fraction methanol: n-hexane (1:1) was 0.0249%. Characterization using spectrophotometer UV-Vis showed a maximum absorption at wavelength of 447 nm which is the absorption of carotene compound. FTIR analysis showed that samples generally have -CH2-, C=C and OH strecth wich are the characteristic of carotene compound. GCMS analysis showed that dye components which estimated is dihydroxy lycopene of the retention time 10.93 with a molecular ion peak at m/z 91.